Rationality of Antibiotic Therapy in Patients with Acute Pharyngitis Based on the Centor Score at the First Level Health Facilities - Raditya, I Gede Wahyu Adi; Putra, I Dewa Gede Arta Eka (Faculty of Medicine, Public Health, and Nursing, 2025)
Background: Pharyngitis is an inflammation of the pharyngeal wall caused by viruses, bacteria, allergies, trauma, irritants, and others. It is important to determine the cause of pharyngitis to ensure the need for antibiotic therapy, considering the high rate of antibiotic resistance. Objective: This study aims to determine the rationality of antibiotic therapy in patients with acute pharyngitis based on the Centor score at the primary health facility in Denpasar. Method: This study is a retrospective descriptive study by taking secondary data from medical records of patients with acute pharyngitis who received antibiotic therapy at Public Health Center A in East Denpasar and Clinic B in West Denpasar. From each primary health care, research samples were selected using systemic random sampling. The Centor score was assessed from the medical records of 32 patients at each primary health care. Rational antibiotic therapy is defined at a Centor score ≥4, while irrational <4. Results: The Centor score description in the sample shows that most samples have a Centor score of less than 4, where in the Public Health Center there were 23 (71.9%) samples and in the Clinic 22 (68.8%) samples. Overall, 45 (70.3%) samples had a Centor score <4, so in this study, only 29.7% of acute pharyngitis patients were rational to receive antibiotic therapy. Conclusions: The administration of antibiotics to patients with acute pharyngitis in primary health care in Denpasar is not rational. Socialization and education are needed for general practitioners in primary health care about the use of the Centor score in patients with acute pharyngitis to help clinicians determine whether or not antibiotic therapy is needed.